EFEKTIVITAS PEMBUBUHAN KAPORIT DALAM MENURUNKAN KADAR ZAT BESI (Fe) PADA AIR SUMUR GALI TAHUN 2013 - Faradillah Azzahrah; Andi Susilawaty (Universitas Islam Negeri Alauddin Makassar, 2014)
Ground water often contains iron (Fe) is quite large. That it contains iron (Fe) in the wa-ter can cause the color of the water turns yellow brown after a while contact with air. At-tempts to obtain water with iron levels are eligible, do not always have the sophisticated technology but could also be using chemicals like the simplest way and do not require great effort and cost in use, one of which is by way of affixing chlorine.This study aims to determine how much chlorine affixing effectiveness in lowering levels of iron (Fe) in the dug well water. This type of research is the design of Quasi-Experiments (Quasi-Experiment Design) using a time series design (Time Series Design), which uses la-boratory tests. Samples taken as much as 28 liters of water in which the sample for the pre-test while the other sample is done by providing chlorine treatment at a dose of 1.5 mg / l, 2.0 mg / l, and 2.5 mg / l with a settling time of 30 minutes, 60 minutes and 90 minutes.The results showed that iron (Fe) in water wells dug by the settling time 30 minutes look after affixing chlorine with a dose of 1.5 mg / l decrease of 16.66%, a dose of 2.5 mg / l of 22.6% , 2.5 mg / l at 28.37%. Later in the deposition time of 60 minutes after affixing chlo-rine with a dose of 1.5 mg / l decrease of 24.75%, a dose of 2.0 mg / l at 34.15%, and at a dose of 2.5 mg / l down 45, 70%. While at the time of deposition 90 minutes after affixing chlorine with a dose of 1.5 mg / l decrease of 37.12%, a dose of 2.0 mg / l at 49.00%, and a dose of 2.5 mg / l decrease by 50 , 16%%.To address water quality dug well that levels of substance iron (Fe) is more than the standard, it can be used chlorine as a water treatment dug wells to get clean water that meets health requirements. It is advisable for people to use a dose of 2.5 mg / l after 90 minutes set-tling time. To study further examination of other chemical parameters such as organic com-pounds that can be known whether the chlorine also can decrease these parameters.K eywords : Effectiveness of Application of Chlorine, Iron (Fe), Wells galley